Bezoar in upper gastrointestinal endoscopy: A single center experience - Gökbulut, Volkan; Kaplan, Mustafa; Kaçar, Sabite; Akdoğan Kayhan, Meral; Coşkun, Orhan; Kayaçetin, Ertuğrul (Turkish Journal of Gastroenterology, 2020)
Background/Aims: We aimed to investigate the association of bezoar with endoscopic findings, risk factors for bezoar occurrence, and the success of endoscopic treatment in a tertiary center.Materials and Methods: This retrospective study was conducted between January 2012 and December 2015. Overall, 8200 endoscopy records were examined and 66 patients with bezoar were included in the study.Results: We enrolled 29 (44%) female and 37 (56%) male patients in this study. The mean age of the patients was 63±9.4 years. The most frequent risk factors were history of gastrointestinal surgery (23%), diabetes mellitus (17%), trichophagia (9%), and anxiety disorder (6%). Gastric ulcer, duodenal ulcer, erosive gastritis, and reflux esophagitis were present in 27%, 11%, 20%, and 23% of the patients, respectively. While bezoars were most commonly observed in the stomach (70%), the majority of them were phytobezoars (91%). The mean number of interventions for each patient was 1.5 (range, 1-6). Endoscopy was successful in removing bezoars in 86.5% of the patients. Among those referred to surgery, seven patients underwent gastrostomy (10.5%); one (1.5%) patient underwent gastroenterostomy because of concomitant pyloric stenosis; and one (1.5%) patient underwent fistula repair surgery due to the development of duodenal fistula caused by bezoar.Conclusion: The findings of this study indicated that bezoars are more common among subjects with history of gastrointestinal surgery, diabetes mellitus, or psychiatric disorders; bezoars are closely related to peptic ulcer and reflux esophagitis; and they can be successfully treated with endoscopy.